Non-adherence to cervical cancer screening recommendations among women in Eswatini: a cross-sectional study - Phinda G. Khumalo; Mariko Carey; Lisa Mackenzie; Rob Sanson-Fisher (BMC, 2023)
Abstract Background In 2018, Eswatini had the world's highest age-standardised cervical cancer incidence rate. Cervical cancer screening reduces women's risk of invasive cervical cancer. Data on adherence to cervical cancer screening recommendations in Eswatini are scarce. The purpose of the current study was to determine Eswatini women's self-reported adherence to cervical cancer screening recommendations, attitudes toward screening, and factors associated with non-adherence. Methods A cross-sectional survey of women (n = 377) aged 25 to 59 accessing primary healthcare clinics (n = 4) in Eswatini assessed screening participation, attitudes and knowledge regarding cervical cancer screening, and socio-demographic variables. Adjusted logistic regression was used to assess factors associated with non-adherence to Eswatini cervical cancer screening recommendations. Results One hundred and sixty-six (44%) women were classified as adherent to cervical cancer screening recommendations. Attitudinal barriers endorsed by over one-third of participants included a perceived low risk of cervical cancer (n = 161, 43%) and a view that screening is likely to be painful (n = 146, 38%). Participants had higher odds of being classified as non-adherent if they: were single compared with married (OR = 1.78, 95% CI: 1.05, 3.01, p = 0.03), perceived screening as likely painful (OR = 4.43, 95% CI: 2.62, 7.46, p < 0.001); and had not been advised by a doctor/ nurse to screen (OR = 2.82, 95% CI: 1.71, 4.64, p < 0.001). Also, a 1-year increase in age was associated with an increase in the odds of being classified as non-adherent (OR = 1.42, 95% CI: 1.39, 1.45, p = 0.01). Conclusions Self-reported adherence was moderate among this group of women. Tailored interventions are needed to increase participation in cervical cancer screening, especially for those women with characteristics associated with being classified as non-adherent. Primary healthcare clinic nurses (and other health providers) may contribute toward improving participation in cervical cancer screening by advising eligible women to screen and providing health education addressing negative attitudes toward screening.